Diagnostic Accuracy of Magnetic Resonance Imaging for Detection of Metastatic Cervical Nodes at Level I and II in Patients with Oral Squamous Cell Carcinoma Taking Postoperative Histopathology as Gold Standard - Muhammad Nauman, Ashfaq-ur-Rahim, Sadiq Ali, Asif Ali, Abdullah Khan, Urooj Kirmani, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Head and neck carcinoma is the malignant lesions which develops on lips, oral cavity, nasal mucosa, paranasal sinuses, inside or outside the throat or parotid glands. Magnetic resonance imaging can be a good alternative to invasive procedures for detection of metastatic disease in cases of head and neck tumors. Objective: To evaluate diagnostic accuracy of magnetic resonance imaging in detecting metastasis in neck nodes of oral squamous cell carcinoma with reference to postoperative neck histopathology. Study Design: Cross sectional study Place and Duration of Study: Department of Oral and Maxillofacial Surgery, Mayo Hospital Lahore from 1st January 2014 to 30th June 2014. Methodology: Eighty seven patients with biopsy proven squamous cell carcinoma of orofacial origin were enrolled who had single malignant tumor at the time of diagnosis. Results: The mean age of the patients was 50.44±12.44 years. There were 58 (66.67%) males and 29 (33.33%) females. In terms of sensitivity, specificity, and diagnostic accuracy, magnetic resonance imaging was 94.12%, 61.11%, and 80.46% respectively taking histopathology as gold standard. Conclusion: For the detection of cervical nodal metastases in oral squamous cell carcinoma, MRI is a useful and trustworthy method with a high sensitivity and specificity, especially when compared to postoperative neck histopathology. Keywords: Histopathology, Carcinoma, Magnetic resonance imaging (MRI),Metastasis